(untitled) (Research, Society and Development, 2022)
Trauma to the woman’s perineum is often seen in vaginal delivery. Its occurrence depends on factors that are related to maternal and fetal conditions, the birth itself and the practice of episiotomy, thus showing the need for strategies to reduce the chances of perineal trauma occurrences. The objective of this work is to identify which strategies are used to minimize perineal trauma, based on an integrative literature review with a qualitative approach and a descriptive study. As inclusion criteria: articles in Portuguese and English, in a period of 10 years, with abstracts available in selected computerized databases. Fifty-one articles emerged in the literature that responded to the research objective, after applying the eligibility criteria, 10 articles remained. Thus, it was found that the strategies used, when necessary, are associated with fewer perineal lacerations and lower rates of episiotomy. Therefore, the following results were found: Encouraging upright position, spontaneous pushing, encouraging water births, vaginal delivery as a protective factor for perineal laceration and expectant, hands off perineal protection. It was noted that the obstetric practices used by professionals to reduce and/or minimize perineal trauma at childbirth, contributed to increasing the rates of perineal integrity and reducing the number of episiotomy; in order to prevent the physical and psychological damage that can result from complications caused by severe lacerations and episiotomy in the female perineum. However, there is a need for further studies, due to the relevance of the theme for women’s health, in addition to contributing to the progress of scientific knowledge.